Storytelling and Listening to Stories A Critical Skill for Early Reading - Soni, Romila (JOURNAL OF INDIAN EDUCATION, 2021)
National Education Policy (NEP) 2020 has put an unprecedented emphasis on developing critical foundational literacy and numeracy (FLN) skills across the foundational stage. In order to improve the foundational literacy competencies and skills of all children at the foundational stage of learning, i.e., from preschool to Class II, various pedagogical practices need to be designed and used in the classrooms and at home. Storytelling is considered as one of the best methods to develop basic literacy skills in young children. Through storytelling, one (teacher or parent) can establish connections easily with other domains or subjects as it motivates children and arouse their interest towards learning. This also enhances children’s competencies in other developmental areas. Use of appropriate pedagogy to promote foundational literacy is an important issue because the success in later years of school education depends on the FLN skills developed during foundational or early years of learning. This article discusses various dimensions of storytelling as a pedagogy and how it develops and boosts the foundational literacy skills in young children.